Effectiveness of eco public art for urban back lanes revitalization - Syamim binti Azhari (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2016)
Back lane is part of cities that is often associated with unutilized issues, leading to several environmental issues, safety problems and the low level of environmental awareness and concerns on its care. Some cities have undertaken revitalization projects through public art as part of the transformation. Therefore, the aim of this research is to examine the revitalization process of an urban back lane through eco public art to identify the steps involved in transforming the back lane, and how eco public art acts as a medium to increase people's environmental awareness. The case study selected is Laman Seni 7, Shah Alam, which is an urban back lane that has been transformed through eco public art. The research methods consist of a site inventory, semi-structured interviews and survey questionnaires. Four key points summarize the revitalization strategy. First, the revitalization process of Laman Seni 7 involved four main phases, which are planning, designing, executing and programming. Second, public preferences of the eco public art were found to be based on specific attributes from the aspects of physical, social, material and message. Third, the findings reveal that eco public art contributes to the increase of environmental education and environmental awareness among the public. Finally, the research concludes that eco public art is indeed an effective medium for urban back lane revitalization. In conclusion, this research contributes to the field of landscape architecture and urban design by recommending a guideline on implementing eco public art for public space that can be adapted by the local authority, designers and the community for back lane revitalization projects in the future.